2015
DOI: 10.1016/j.icarus.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

New Horizons: Long-range Kuiper Belt targets observed by the Hubble Space Telescope

Abstract: We report on Hubble Space Telescope (HST) observations of three Kuiper Belt Objects (KBOs), discovered in our dedicated ground-based search campaign, that are candidates for long-range observations from the New Horizons spacecraft: 2011 JY 31 , 2011 HZ 102 , and 2013 LU 35 . Astrometry with HST enables both current and future critical accuracy improvements for orbit precision, required for possible New Horizons observations, beyond what can be obtained from the ground. Photometric colors of all three objects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…COLOR, BINARITY, SIZE AND VARIABILITY FINDINGS Table 3 lists the observed colors of the KBOs from this program. In Figure 3 we then compare this newly obtained data with 145 KBO colors that have been previously measured using the same HST filters (Benecchi et al 2009;Fraser et al 2012;Benecchi et al 2015). The F606W-F814W colors (a proxy for V-I) plotted span a wide range from 0.5 < F606W-F814W < 1.3.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…COLOR, BINARITY, SIZE AND VARIABILITY FINDINGS Table 3 lists the observed colors of the KBOs from this program. In Figure 3 we then compare this newly obtained data with 145 KBO colors that have been previously measured using the same HST filters (Benecchi et al 2009;Fraser et al 2012;Benecchi et al 2015). The F606W-F814W colors (a proxy for V-I) plotted span a wide range from 0.5 < F606W-F814W < 1.3.…”
mentioning
confidence: 85%
“…Color results for all long-range New Horizons targets with HST colors compared with the colors of all other KBOs that have been measured in the same HST filters (from Benecchi et al 2009, Fuentes et al 2010Fraser et al 2012 andBenecchi et al 2015) with respect to their direct F606W magnitudes. Plotted along the top is an estimate of the effective diameters for these objects following the formulation of Bowell et al (1989) d = 10((6.259−0.4·HF606W −log r)/2) km and assuming an albedo, r; we assume r = 0.12.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…While the secondary targets for New Horizons are even fainter and required the use of HST to discover, the Megacam images can be used to extend the orbital arcs of those targets. The Megacam search yielded the discovery of a new Neptune Trojan (Parker et al 2013) and identified targets that will be examined at long range with New Horizons (Benecchi et al 2015). The Megacam search data, in combination with the HST data, will also be used in refining our understanding of the size distribution of small Kuiper belt objects.…”
Section: Solar System Searchesmentioning
confidence: 99%